INNOVATIVE INSTRUCTIONAL TECHNOLOGIES FOR TEACHING HIGHER-ORDER DIFFERENTIAL EQUATIONS - Maqpal Eraliyeva (Modern American Journals, 2025)
This article explores the implementation of innovative instructional technologies in the teaching of higher-order differential equations within the context of teacher education in Uzbekistan. As mathematical disciplines become increasingly complex and abstract, effective teaching strategies and the integration of digital tools become essential. The study highlights how technologies such as computer algebra systems, interactive simulations, and blended learning platforms contribute to a more accessible, engaging, and conceptually clear learning experience for university students. Emphasis is placed on pedagogical alignment, cognitive development, and didactic transformation through technology.
Keywords: Higher-order differential equations, innovative teaching methods, educational technology, teacher education, digital learning tools, mathematics instruction.